Backlash over NHS plan to hide source code from AI attack. - Sparkes, Matthew (New Scientist, 2026)
The article focuses on NHS England’s decision to withdraw open-source software code created with UK taxpayer funds due to concerns about AI models, such as Mythos by Anthropic, potentially exposing security vulnerabilities. This move contradicts NHS standards that promote open-source software to encourage collaboration and improvement. An open letter opposing the decision has garnered over 1,100 signatures, including from former UK health secretary Matt Hancock, who called the policy a “huge mistake.” Critics argue that restricting access harms cybersecurity experts who help protect public services, while NHS England states the restriction is temporary to strengthen cybersecurity amid rapid AI developments.